Clinical experience with automatic midline echoencephalography: cooperative study of three neurosurgical clinics. Issue 3 (March 1975) - Klinger, M; Kazner, E; Grumme, T; Amtenbrink, V; Graef, G; Hartmann, K H; Hopman, H; Meese, W; Vogel, B
Abstract : Computerized midline echoencephalography was developed in order to make the determination of the midline more objective. In a group study involving the neurosurgical clinics in Berlin, Erlangen, and Munich, a total of 1, 889 patients with various intracranial diseases was examined by this method. An exact analysis of the results obtained is presented: 18 percent were unsatisfactory.